Implikasi Blockchain dengan Metode Digital Audit Forensik (DAF) pada Korupsi: Analisis Bibliometrik - Najmuddin, Ahmad Bebin; Widihardimas, Tarcisius Jassien; Sulistyawati, Ayu Sarah (Juara: Jurnal Riset Akuntansi, 2025)
This study aims to analyze and map research trends on digital audit forensics (DAF) using blockchain technology in the context of corruption. Bibliometric analysis was used to analyze 39 articles in the Scopus database from 2019-2023, then also using VOSviewer 1.6.18 software and visualized further. This study provides insights and additional contributions to the understanding of digital forensic audits (DAF) using blockchain methods in the context of corruption. These results highlight the growing role of blockchain in enhancing forensic audit practices against corruption and suggest potential directions for future studies, including the integration of artificial intelligence and machine learning. This study provides both theoretical insights and practical references for researchers and practitioners in the field of digital auditing and anti-corruption efforts.